Association of physical activity and vitamin D deficiency with cognitive impairment in older adults: a population based cross-sectional analysis - Guo, Jing; Mo, Hongfei; Zuo, Longfei; Zhang, Xu (Frontiers in Nutrition, 2024)
Objectives The global aging situation is becoming increasingly critical and cognitive impairment in the elderly has become a public health burden of concern. Physical activity (PA) and vitamin D may play a key role in improving cognitive impairment. However, little studies have examined the interaction between these two. The purpose of this study was to assess the association of PA and vitamin D with cognitive impairment in older adults, as well as the interactions of PA and vitamin D. Materials and methods This study was conducted by multi-stage random sampling of elderly people ≥60 years old, and a total sample of 2,492 (1,207 male and 1,285 female, mean age of 69.41 ± 6.75 years) with complete data was included in the analysis. PA was assessed by the Global Physical Activity Questionnaire, and < 600 MET-min/week was used as the division criteria. Serum vitamin D was measured by high-performance liquid chromatography tandem mass spectrometry, and 25-hydroxyvitamin D2/D3 concentration < 20 ng/mL was used as a vitamin D deficiency criterion. Cognitive function was assessed by three subtests: the Consortium to Establish a Registry for Alzheimer’s disease word learning test (CERAD-WL) for immediate and delayed learning, the Animal Fluency Test (AFT) for verbal fluency; and the Digit Symbol Substitution Test (DSST) for information processing speed and switching attention. All three subtests were scored at less than the lowest quartile of the score as a criterion for cognitive impairment. Statistical analysis was performed using SPSS for chi-square test, rank sum test, interaction analysis, subgroup analysis, and regression analysis. Results Lower level of PA is associated with higher odds of cognitive impairment (CERAD W-L: OR = 1.596, 95% CI: 1.338–1.905, p < 0.001; AFT: OR = 1.833, 95% CI: 1.534–2.190, p < 0.001; DSST: OR = 1.936, 95% CI: 1.609–2.329, p < 0.001). Vitamin D deficiency has significant effects in AFT (OR = 1.322, 95% CI: 1.103–1.584, p = 0.003) and DSST (OR = 1.619, 95% CI: 1.345–1.948, p < 0.001). After adjusted for covariates, PA and vitamin D have multiplicative interaction on AFT (OR = 0.662, 95% CI: 0.448–0.977, p = 0.038) and DSST (OR = 0.775, 95% CI: 0.363–0.868, p = 0.009). The interaction between PA and vitamin D was not significant in the CERAD W-L (OR = 0.757, 95% CI: 0.508–1.128, p = 0.172). Conclusion The results showed that lower level of PA and vitamin D deficiency were associated with higher odds of cognitive impairment in the elderly population and that there was a multiplicative interaction between PA and vitamin D on cognitive function, with a significant effect of vitamin D on cognitive impairment in high PA conditions.